Optimal Energy-Efficient Cooperative Spectrum Sensing in Cognitive Radio Networks - Zhang, Zongsheng; Wu, Qihui; Wang, Jinlong (Společnost pro radioelektronické inženýrství, 2013)
Inspired by the green communication trend of next-generation wireless networks, we select energy-efficient throughput as optimization metric for jointly optimizing sensing time and working sensors in cooperative cognitive radio networks. Specifically, an iterative algorithm is proposed to obtain the optimal values for these two parameters. Specifically, the proposed iterative algorithm is low complexity when compares to the exhaustive search method, and very easy to be implemented. Finally, simulation results reveal that the proposed optimization improves the energy-efficient throughput significantly when the sensing time and working sensors are jointly optimized.
Keywords: Energy-efficiency (EE); cognitive radio networks; cooperative spectrum sensing.